Diabetes nursing consultation based on the Sunrise model: A cost-minimization analysis (Research, Society and Development, 2023)
The object of the present study derives from the results of the Professional Master's research entitled “Instrument for the care of pregnant women with Diabetes Mellitus based on the Sunrise model”. Based on the research results, it was possible to develop an instrument based on the Sunrise model, to be used by nurses in a nursing consultation for patients with Diabetes Mellitus. Objective: To analyze the cost- minimization of outpatient use of the instrument based on the Sunrise model for nursing consultations in individuals with Diabetes Mellitus.; To estimate the costs associated with outpatient care for DM1 and DM2 and the costs of hospitalizations avoided with and without the Sunrise model. Methodology: This is a Health Technology Assessment (HTA) study, a type of cost-minimization research; the method used is quantitative. Results: The nursing consultation based on the Sunrise model is capable of reducing the costs of outpatient diabetes treatment. Conclusion: In addition to ensuring better adherence to treatment with reduced costs, the incorporation of technology allows the institution to achieve strategic planning objectives.